On variation in Faroese verb placement - Bentzen, Kristine; Garbacz, Piotr; Heycock, Caroline; Hrafnbjargarson, Gunnar Hrafn (Department of Linguistics, University of Tromsø, 2009)
In this paper, we present and discuss results from an investigation of verb placement in modern Faroese in which we collected data from speakers from a number of different dialect areas in the Faroe Islands. Altogether we interviewed 54 informants (age 15 – 67, 29 women and 25 men). Therefore, our study not only investigates the geographical variation claimed to be present in Faroese with respect to verb placement, but also gender and age variation. Our results indicate that verb movement in non-V2 contexts is no longer commonly available to the speakers of Faroese. Our results also suggest that verb movement across adverbs like often and already tends to be more acceptable than movement across negation and other adverbs like never and undoubtedly. Furthermore, movement of finite auxiliaries generally receives a slightly higher score than movement of finite main verbs. Our results do not show any differences in the judgements of speakers below and above the age of 25. Contrary to Jonas (1996), we find that speakers in the North are, if anything, more likely to accept verb movement than speakers in the South.